PM IRRAS spectroelectrochemistry of layer-by-layer self-assembled polyelectrolyte multilayers - Tagliazucchi, Mario Eugenio (2010)
In situ polarization modulation infrared reflection absorption spectroscopy (PM IRRAS) has been used to study layer-by-layer self-assembled films made of a novel redox polymer bearing an osmium pentacyano pyridine complex (PAH-OsCN) and polyacrylic acid at different electrode potentials and solution compositions. PM IRRAS provides information on the oxidation state of the osmium complex, the fraction of protonated carboxylates and the content of IR-active counterions (such as nitrate) as well as water content (hydratation of the multilayer). It has an advantage over SNIFTIRS because it measures the absolute IR-signal arising from the molecular species at the interface rather than its variation with respect to a reference state. For instance, we show that only a fraction of the total number of redox sites responds to changes in the electrode potential as expected from the Nernst equation. The remaining sites are trapped in the Os(II) or Os(III) states and can only be oxidized/reduced by chemical agents in solution. We also present spectroscopic evidence that nitrate ions enter into the film during oxidation and leave during reduction. The number of these anions involved in the first process is larger than that participating in the latter and hence nitrate accumulates within the film. This finding is analyzed in terms of two possible mechanisms. © 2009 Elsevier B.V. All rights reserved.